Explaining social contagion in sport applying Heider's balance theory: First experimental results. (March 2015) - Boss, Martin; Kleinert, Jens
Abstract: A sudden collective collapse of an entire sport team is often described in terms of the social contagion of weak performance. Two experiments studied this phenomenon against the backdrop of balance theory. Experiment 1 examined whether false negative feedback on a partner's performance during a team task would lead to compensatory mechanisms as predicted by balance theory. Results showed that perceived negative performance in the partner was compensated by devaluing the relationship to the partner. Experiment 2 replicated Experiment 1 and investigated the impact of physical self-esteem. Results showed that persons with strong physical self-esteem devalued the situational value of the relationship when they perceived their partner's performance to be negative. Experiment 2 also investigated objective performance. Although failing to attain statistical significance, there was a tendency for the perceived sudden decline in the partner's performance to be contagious. It is concluded that balance theory offers promising insights into the interpersonal dynamics of social contagion. Highlights: Balance theory is suitable for clarifying social contagion in sport. In cases of imbalance the social relationship is devalued to re-balance the system. The higher the physical self-esteem the higher devaluation of social relationships.